ANALISA KEKUATAN MEKANIS SAMBUNGAN LAS KAMPUH V TUNGGAL DAN V GANDA PADA BAJA KARBON RENDAH DENGAN PROSES PENGELASAN SMAW - Sudarsono Sudarsono; Hidayat Hidayat; Aminur Aminur; Sarwo Pranoto; Prinob Aksar (Dinamika : Jurnal Ilmiah Teknik Mesin, 2021)
Welding is one of the methods widely used in the joining of metals for structural elements. One of the factors that influence the strength of welded metals is types of welding joints. Suitability of the type of welding joint with geometries of base metals is required to obtain welded metal products with optimum properties. In this study an attempt is made to investigate mechanical properties of welded metals with two different types of joints (single-V and double-V) using the shielded metal arc welding (SMAW) process. Low carbon steel with bevel angle of 60° was used in this study. Welding process was performed using current of 70 A with a constant welding speed. The flexural properties and uniaxial tensile properties are studied by three-point bending test and uniaxial tensile test respectively. Test results show that the tensile strength and the bending strength of single-V specimens is 521.64 N/mm2 and 525.11 N/mm2 respectively. In addition, the tensile strength and the bending strength of double-V specimens is 517.33 N/mm2 and  504.24 N/mm2 respectively